DEPRESSIVE DISORDERS IN PATIENTS WITH CARDIOVASCULAR DISEASE: DETERMINING THE PROGNOSIS - D. N. Ivanchenko; N. P. Dorofeeva; S. V. Shlyk (Медицинский вестник Юга России, 2016)
Despite the advances in the diagnosis and treatment of cardiovascular diseases, the cardiac mortality takes a leading position among the causes of general mortality. It was also noted that depressive disorders are widespread among the cardiovascular patients. They induce the impairment of cardiac prognosis both in patients with cardiovascular disease and in patients without cardiac disease. The article outlines the basic pathophysiological mechanisms of interaction between depressive symptoms and cardiovascular disease. In addition, the article focuses on the diagnosis of depressive symptoms as a factor determining cardiac prognosis.